Development and Optimization of Mathematical Models for Operations Research - Rocha, Humberto; Rocha, Ana Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The development of mathematical models and their optimization are fundamental for the effective resolution of many problems in operational research. In recent years, increased insights into real-world problems have led to the development of new mathematical models and optimization algorithms, contributing to the development of a research area with increasing practical relevance. This Special Issue is dedicated to works at the interface of mathematical modeling, optimization, and operations research, with a special focus on their real-world applications. The interest of the scientific community was significant, with submissions from authors from different countries from five continents, including Australia, China, Egypt, India, Israel, Portugal, Russia, Saudi Arabia, and the United States of America. Ten papers were accepted for publication after thorough peer review by dedicated reviewers with expertise in the relevant fields. We are confident that the papers selected for this Special Issue will attract a significant audience in the scientific community and will further stimulate research involving the development of mathematical models and their optimization.